Tri/Celcom: Fixed Services Division Strategic Analysis Factors and Strategies - Ghazali, Siti Norainul Azam (1998)
Cellular Communications Network Sdn Bhd was formed as a private limited company in January 1988, under the name of STM Celullar Communications Sdn Bhd which was initially owned by Syarikat Telekom Malaysia(STM), now known as Telekom Malaysia. In December 1989 after it has commenced operation STM sold 51%of its stake to Alpine Resources Sdn Bhd. During this time the Cellular Communications Net work SIB customers base is already about 6,800 subscribers. The company later changed its name to Celcom Sdn Bhd. Technology Resources Indutsries (TRI) was incorporated in 1 966 as a private limited comp any in Malaysia and its shares was listed on the Kuala Lumpur Stock Exchange in 1971. TRI was initially known as Roxy Electric Industries Sdn Bhd. TRI indirectly held 51% stake of Cellular Communications Network Sdn Bhd through its subsidiary company Alpine Resources Sdn Bhd and later TRI/Celcom was eventualy formed when TRI acquired the remaining 49% equity interest in Cellular Communications Newtork(Malyasia) Sdn Bhd for RM271,705,000 and RM14,700,000 representing 36,75 0,000 ordinary shares of RM1 RM14,700,000 (8%) Irredeemable convertible cumulative preference shares of RM1.00 each respectively. The Cellular Communications Newtork(Celcom)was initialy set up back in 19 TRI/Celcom held majority shareholders of Celcom as well as several other companies such as Alpine Resources(100%equiyt interest), TR International Ltd, TR(USA) Ltd, and Celcom Ventures (Malaysia) Sdn Bhd as wholly owned subsidiaries.